Characterization of nanoliposomes loaded with saffron extract: in vitro digestion and release of crocin - Saroglu, Oznur; Atali, Busra; Yildirim, Rusen Metin; Karadag, Ayse (SPRINGER, 2022)
Nanoliposomes (NLs) (70 nm) loaded with saffron extract were produced by high-pressure homogenization and coated with chitosan with different molecular weights. The liposomal dispersions were converted to spray-dried powders afterward. The encapsulation efficiency of crocin in the NLs reached 75.86%. Upon reconstitution of spray-dried liposomes, a higher increase in size was observed in uncoated liposomes (2.8-fold) compared to chitosan-coated ones (1.8-fold). Under the acidic conditions (pH 3.5), the crocin loss was 86% in free extract, whereas only 7-20% of crocin loss was observed in liposomal samples after 48 h of incubation. When the samples were subjected to in vitro digestion, the retention of crocin in liposomal structures (71.02-92.63%) was higher than that of free saffron extract (50.72%). The release data of crocin from liposomes was best fitted to the Higuchi diffusion model and the release of crocin was sustained over time. The release rate constant was reduced by the encapsulation, the highest value (40.51) was observed in the free extract and low molecular weight chitosan-coated NLs exhibited the lowest release rate constant (5.58 and 4.44). Nanoliposomal encapsulation of saffron extract provided higher acid stability, sustained-release properties, and protection of crocin under in vitro digestion conditions.
Keywords: Crocus sativus L; Spray-dying; Chitosan; pH stability; In vitro digestion; Sustained release; ORAL BIOAVAILABILITY; LIPOSOMES; STABILITY; ANTIOXIDANT; ENCAPSULATION; FOOD; CURCUMIN; DELIVERY; CHOLESTEROL; Food Science & Technology